Analysis of the linearity relation between the tutor’s actions and the learners’ interactions in Distance Education courses - Amaral, Ygor; Rodrigues, Rodrigo L.; Soares, Fabiana; Gonçalves, Angelo F. Dias; Maciel, Alexandre M. A. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2015: Anais do XXVI Simpósio Brasileiro de Informática na Educação, 2015)
It has been a challenge to extract relevant information that lead to a more effective understanding of the interactions between students and tutors in Distance Education (DE) courses. This work aims at presenting this relation through statistics analyses based on multiple linear regression algorithms and on Educational Data Mining (EDM). It is proposed the use of linear regression technique to estimate the level of interactions of students based in behavioral variables of the tutors. The results showed that it is possible to use the linear regression technique in order to get inferences with good precision rates with respect to the relation between the tutors’ actions in the Learning Management System and the increase of students’ interactions.